Update on Sepsis Epidemiology in the Era of COVID-19 - Shappell, Claire; Rhee, Chanu; Klompas, Michael (Seminars in Respiratory and Critical Care Medicine, 2023)
Timely and accurate data on the epidemiology of sepsis is essential to inform public policy, clinical practice, and research priorities. Recent studies have illuminated several ongoing questions about sepsis epidemiology, including the incidence and outcomes of sepsis in non-Western countries and in specialized populations such as surgical patients, patients with cancer, and the elderly. There have also been new insights into the limitations of current surveillance methods using administrative data and increasing experience tracking sepsis incidence and outcomes using “big data” approaches that take advantage of detailed electronic health record data. The COVID-19 pandemic, however, has fundamentally changed the landscape of sepsis epidemiology. It has increased sepsis rates, helped highlight ongoing controversies about how to define sepsis, and intensified debate about the possible unintended consequences of overly rigid sepsis care bundles. Despite these controversies, there is a growing consensus that severe COVID-19 causing organ dysfunction is appropriate to label as sepsis, even though it is treated very differently from bacterial sepsis, and that surveillance strategies need to be modified to reliably identify these cases to fully capture and delineate the current burden of sepsis. This review will summarize recent insights into the epidemiology of sepsis and highlight several urgent questions and priorities catalyzed by COVID-19.
Keywords: sepsis epidemiology; COVID-19; SARS-CoV-2